EXPLORING GENDER EQUITY AND EMPOWERMENT IN EDUCATION IN THE CONTEXT OF NAGALAND - Zeliang, Lungsang; Malakar, Durga (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study explores the undercurrents of gender equity and empowerment within educational institutions. Education is regarded as the most pivotal tool for the all-round development of individuals. Gender discrimination, especially in education, is prevalent in the world over. This study tries to understand the barriers and facilitators influencing gender parity and the empowerment of girls and women in educational settings. The study will seek to identify the factors that hinder gender equity in Nagaland, India, such as enrolment, retention, curriculum, and the impact of socio-cultural factors. There has been significant progress in the education of girls and women, but disparities persist, especially in marginalised communities. Several factors, such as poverty, sociocultural norms, infrastructure, and curriculum, continue to impede the educational advancement of women. The paper explores the necessity of a multi-faceted approach that addresses these challenges. The study presents a way forward for policymakers and stakeholders to promote gender equity and empower girls and women through education in Nagaland and the country. The present paper also tries to understand why women have little say in decision-making, political participation, and administration despite being well-educated.